PENGARUH DIMENSI KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN KARTU SELULER XL (STUDI KASUS PADA MASYARAKATNAGARI TALANG BABUNGO KEC. HILIRAN GUMANTI KAB. SOLOK - Febriati, Roza; Dewita, Yulna Hia; Natassia, Rizky (Pendidikan Ekonomi, 2014)
ABSTRACTIssues that are examined in this study is the effect of product quality dimensions on consumer loyalty XL mobile card on society of Nagari Talango Babungo Kec. Hiliran Gumanti Kab. Solok. The purpose of this study was to analyze the effect of performance (X1), durability (X2), ease of repair (X3), features (X4), reliability (X5), aesthetics (X6), and the impression of quality (X7) on consumer loyalty card cellular XL on society of Nagari Talang Babungo Kec. Hiliran Gumanti Kab. Solok. The technique of collecting data using questionnaires, the data were analyzed by linear regression method berganda.Hasil research shows that First : performance a positive and significant effect on consumer loyalty XL mobile card indicated by the coefficient value of 0.291 with a test value of thitung is 4.768 and significant at 0.000 < α = 0.05 . Second : durability a positive and significant effect on consumer loyalty shown by the coefficient value of 0.051 with a test value of thitung is 1.123 and the value of the test is significant at 0.045 < α = 0.05 . Third : ease of repair a positive and significant effect on consumer loyalty shown by the coefficient value of 0.286 with a test value of thitung is 4.764 and significant at 0.000 < α = 0.05 . Fourth : features a positive and significant effect on consumer loyalty shown by the coefficient value of 0.012 with a test value of thitung is 0.238 and significant at 0.024 < α = 0.05 . Fifth : reliability a positive and significant effect on consumer loyalty shown by the coefficient value of 0.154 with a test value of thitung is 2.354 and significant at 0.019 < α = 0.05 . Sixth : aesthetics a positive and significant effect on consumer loyalty shown by the coefficient value of 0.104 with a test value of thitung is 2.167 and significant at 0.0,031 < α = 0.05 . seventh : the quality impression a positive and significant effect on consumer loyalty shown by the coefficient value of 0.256 with a test value of thitung is 5.426 and significant at 0.000 < α = 0.05 . Test Fhitung 42.666 with significant value of 0.000 < α = 0.05 and test the coefficient of determination ( R Square) of 73.3 % , while the remaining 26.7 % is explained by other variables or causes beyond regression models of this study . Based on the results of this study concluded that all dimensions of quality products and a significant positive effect on consumer loyalty in the XL mobile card purchase products on society of Nagari Talang Babungo Kec. Hiliran Gumanti Kab. Solok.